PENYIDIKAN TINDAK PIDANA PERBANKAN DALAM BENTUK KREDIT FIKTIF PADA BANK PERKREDITAN RAKYAT (BPR) MITRA DANAGUNG (Studi Pada Satreskrim Polres Pesisir Selatan) - Ansari, Ichsan (Universitas Ekasakti, 2021)
Article 49 of Law no. 10 of 1998 concerning Banking has explicitly regulated criminal acts related to bank business. However, there are still many parties who commit criminal acts in the banking sector, one of which is fictitious credit. Like the fictitious credit that happened to the Rural Bank (BPR) Mitra Danagung, which was carried out by the Director of Bank Mitra Danagung himself, in the period from 2011 to 2012. The formulation of the problems studied in this thesis are: First, how is the investigation of banking crimes in the form of fictitious loans at BPR Mitra Danagung Bank? Second, what are the obstacles faced by the Satreskrim Investigator of the Pesisir Selatan Police in the investigation of banking crimes in the form of fictitious credit at Bank BPR MitraDanagung? This research is a legal research with a descriptive analytical specification. The main approach used is a normative juridical approach and is supported by an empirical juridical approach. The data used are secondary data as primary data, and primary data as supporting data collected through library research and field research. The data is then analyzed qualitatively and presented in a qualitative descriptive form. Based on the results of the study, it can be concluded, first, that the investigation of banking crimes in the form of fictitious credit at PBR Mitra Danagung Bank was carried out based on the principle of lex specialis derogat legi generalis. After receiving the report, the investigative team conducts an investigation and review of the report to prepare a plan for investigative activities, followed by examining witnesses and collecting evidence and expert testimony, then a case is held to determine the suspect, then arrests and detentions are made. After the filing is complete, the investigator submits the case file to the Public Prosecutor accompanied by witnesses and evidence. Second, the obstacles faced by the investigators of the Satreskrim Polres Pesisir Selatan in the investigation of banking crimes in the form of fictitious credit at Bank BPR Mitra Danagung are: the overlapping authority of investigating banking crimes as regulated by a law that gives authority to the Police, Prosecutors, and Investigators. OJK, limited human resources for investigators, level of education and low knowledge of investigators about advances in information technology, as well as supporting facilities and infrastructure in conducting investigations.